The Performance Evaluation of a Horizontal Capstan in the Lori Pulling System at Bah Jambi Palm Oil Mill - Lamlam Jeki Padang; Busrizal Faisal (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study evaluated the performance of a horizontal capstan used in the lori pulling system at Bah Jambi Palm Oil Mill. The study focused on the operational relationship among gearbox pulley rotation, lubricant viscosity, gearbox/oil temperature, and lori pulling time as indicators of capstan effectiveness. Field observations were conducted from 11 to 25 May 2026 by measuring motor speed, pulley dimensions, wire rope diameter, shaft spacing, oil viscosity, gearbox/oil temperature, and lori pulling time. Gearbox pulley speed was calculated from the pulley ratio, while changes in viscosity, temperature, and pulling time were analyzed descriptively to assess the operating condition of the capstan system. The results showed that the gearbox pulley rotated at 13 rpm, indicating an effective speed reduction mechanism for generating the torque required to pull sterilizer lorries. During the observation period, oil viscosity decreased from 30.71 cSt to 21.63 cSt, equivalent to a reduction of 29.57%, while gearbox/oil temperature increased from 41.77°C to 45.47°C. Despite lubricant degradation, lori pulling time remained relatively stable within 137.33–143.67 s, indicating that the capstan continued to operate effectively. Overall, the horizontal capstan at Bah Jambi Palm Oil Mill remained operationally reliable during the study period, although the decline in lubricant condition suggests the need for periodic monitoring and maintenance to preserve long-term transmission performance.